Caregivers’ perceptions of vaccination against COVID-19 infection in the city of Kinshasa: The case of Kintambo General Referral Hospital, Kinshasa, Democratic Republic of the Congo - Kanyere Saa-Sita, Chantal; KADIATA BUKASA, Augustin; Masengu Badibanga, Rachel; Mufaume Sifa, Sophie; Sebo Mbioka , Christiane (Orapuh Journal, 2026)
IntroductionFollowing the declaration of the COVID-19 pandemic, the Democratic Republic of Congo (DRC), under the coordination of the Presidency of the Republic through the Multisectoral Response Committee against COVID-19, implemented measures recommended by the World Health Organization, including screening, adherence to barrier measures, and vaccination.PurposeThis study aimed to explore healthcare workers’ perceptions of and attitudes towards COVID-19 vaccination at Kintambo General Referral Hospital in Kinshasa, and to identify factors influencing vaccine acceptability, hesitancy, and refusal.MethodsAn exploratory qualitative study was conducted among healthcare workers at Kintambo General Referral Hospital. Data were collected using surveys and semi-structured interviews and analysed through thematic and categorical analysis.ResultsInitial perceptions of the COVID-19 vaccine were largely negative, with the vaccine perceived as a poison, a tool for population control, a masquerade, or a population sterilisation strategy. Over time, these perceptions became more positive, with vaccination increasingly viewed as a protective measure with moderately accepted effectiveness. Vaccine acceptability depended on production by a reputable laboratory, absence of significant side effects, and voluntary administration. Motivations for vaccination included perceived occupational exposure to COVID-19 and professional responsibility. Reasons for refusal included misinformation disseminated on social media, controversies surrounding early vaccines, limited knowledge about COVID-19, doubts about vaccine safety and effectiveness, fear of side effects, and the politicisation of vaccination.ConclusionThe findings indicate that concerns about COVID-19 vaccination persist among healthcare workers. Strengthening targeted awareness and communication strategies that clearly explain scientific evidence and clinical trial results is essential to improve confidence in vaccines. Addressing misinformation and promoting evidence-based decision-making are critical to enhancing vaccine acceptance among healthcare workers and the general population.